Role of Cost Efficiency, Capital Leverage, and Cost of Capital in Determining Shareholders' Value - István Zsombor Hágen; Amanj Mohamed Ahmed (Ital Publication, 2026)
The objective of this research is to explore the impact of cost efficiency, capital leverage, and cost of capital on shareholder value regarding the GCC, a dynamic and inventive economy. Data from 41 banks that were listed on the stock exchange from 2015 to 2023 were collected. The Refinitiv Eikon interface provided bank-level data to achieve the aim of this study. GLS with cross-sectional weight as a panel econometric method was applied. The findings display that cost efficiency has a significant impact on shareholder value in the GCC banking sector. Reduced operational expenses, increased asset utilization, and effective tax planning have a positive effect on shareholders' return. Although financing with debt has a minimal effect on GCC banks' productivity, it is nevertheless important for evaluating the market performance, with DMC possessing a negative effect and DTA holding a positive influence. Moreover, revenue generation and the value of shareholders are all continuously improved by an optimum cost of capital (WACC). The outcomes of this study enrich the current literature by proposing a combined framework for assessing cost efficiency, capital leverage, and cost of capital. It also fills the gap in earlier regional research by providing new perspectives for creating shareholder value in the GCC banking industry.